Emerging treatments for cluster headache: hopes and disappointments. Issue 3 (June 2019) - Magis, Delphine
Abstract : Purpose of review: Cluster headache stands among the worst debilitating pain conditions. Available treatments for cluster headache have often disabling side effects, are not tolerated, or are ineffective. The management of drug-refractory chronic forms is challenging. New treatments are warranted and reported here. Recent findings: In cluster headache acute treatment, delivery systems like Demand Valve Oxygen or nonrebreather-type masks could enhance the effectiveness of inhaled oxygen therapy. Noninvasive vagus nerve stimulation relieves cluster headache pain at short-term in episodic patients. Sphenopalatine ganglion stimulation combines acute and preventive properties in subsets of patients and is of interest in selected refractory chronic forms. In cluster headache prevention, 'hypothalamic' deep brain stimulation is being refined using slightly different stereotactic coordinates or lower risk methods like endoventricular stimulation. Anti-CGRP monoclonal antibodies provide interesting results in episodic cluster headache, have a good safety profile, but do not appear effective in chronic cluster headache. Summary: These novel approaches provide additional alternatives to conventional cluster headache management, but results obtained in chronic forms are often disappointing. Research on cluster headache is often hampered by the lack of awareness in the medical world and by the relatively low prevalence of cluster headache compared with migraine. However, common features shared by these two primary headaches could help developing disease-specific therapies.